FUNGSI MANAJEMEN DALAM PENINGKATAN DISIPLIN KERJA APARATUR DI KANTOR KOMISI PEMILIHAN UMUM (KPU) PROVINSI SULAWESI TENGAH - Parakkasi, Palman (Katalogis, 2017)
This study used a qualitative descriptive approach. The data is collected by doing observation, interview, and documentation. This research has five informants. The data analysis techniques in this study follows the three stages, namely : data reduction, data display, and conclusion or verification. Theory of George R.TerryWhich is included four aspects of Planning-Organizing, Actuating and Controlling is choosen as a framework theory in improving the discipline of apparatuses. From the research found the fact that the KPU organization has done a plan to improve the discipline apparatuses based on the regulation of ASN. So that the apparatuses can adapt to the changing demands of technology. KPU organization also has been organizing the discipline improvement of apparatuses based on the regulation of ASN therefore personnel can carry out organizing well. Mobilization ( Actuating) personnel who work within an organization (In KPU) has a different background either education, expertise, experience and their culture, so that, they be able to improve the discipline in an integrated vision. ( Controlling ) Leadership element, which has the authority to supervise the discipline of apparatuses in the office of KPU, has not been going well. There are still exist apparatuses who have not been discipline in completing the work on time.